Integrated molded inductor and preparation method thereof

By using composite magnetic powder to prepare an integrated molded inductor, the problem of insufficient temperature resistance in high-temperature environments is solved, and the high-temperature stability and reliability of the inductor are achieved.

CN119381157BActive Publication Date: 2025-02-28TDG HLDG CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411961276.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-02-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing integrated molded inductors have insufficient temperature resistance levels in high temperature environments, which cannot meet the reliability requirements of high temperature environments such as automotive electronics.

Method used

Composite magnetic powder is used as the filling material. The composite magnetic powder is composed of insulating agent, epoxy resin, cyanate resin, liquid polysulfide rubber, curing catalyst, etc., and an integrated molded inductor is prepared through die-casting and thermal curing processes.

Benefits of technology

The high temperature resistance of the inductor is improved, so that it can cure at a temperature below 180°C, avoid cracking problems during thermal curing, and meet the reliability requirements in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of inductor preparation, and discloses an integrally formed inductor and a preparation method thereof, the preparation method comprising: placing a winding coil in a mold; filling the mold with a mixed powder, the mixed powder comprising a lubricant and a composite magnetic powder; die casting, and then thermal curing; the components of the composite magnetic powder comprising: an insulating agent, a first adhesive, a second adhesive, a third adhesive, a low-temperature curing agent, a curing catalyst, and passivated magnetic powder; the first adhesive is selected from at least one of epoxy resin, phenolic resin, and polyurethane; the second adhesive is a cyanate resin; and the third adhesive is selected from at least one of liquid polysulfide rubber and polycarbonate. The preparation method can produce an inductor with no cracking and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inductor manufacturing, and in particular to an integrally formed inductor and a preparation method thereof. Background Art

[0002] With the development of computer central processing units (CPUs), field programmable gate arrays (FPGAs), and various types of chip-based application-specific integrated circuits (ASICs), low voltage and high current have become the development trend of DC-DC power supplies. In order to obtain high-current circuit technology, not only a single DC-DC converter power supply circuit is used, but now a multi-phase power supply circuit composed of several DC-DC converters has become the mainstream. With the multi-phase power supply circuit technology, the number of power inductors required has further increased. Compared with previous products, corresponding space saving and high-density assembly technology urgently require power inductors to be further miniaturized and thinned.

[0003] The one-piece molded inductor has the characteristics of small size, high performance, low power consumption, low noise, moisture resistance, vibration resistance, etc., and has a high operating frequency. It can be widely used in next-generation mobile devices, desktop computers, servers, graphics cards and automotive systems, ultra-thin high-current power supplies and load point (POL) converters, distributed power systems and FPGA and other terminal products.

[0004] In the selection of powder materials for integrated molded inductors, since the inductor works under high current conditions, the material is required to have good DC superposition characteristics. Traditional ferrite materials have low saturation magnetization and weak DC resistance, while iron powder core soft magnetic composite materials with high saturation magnetization, low medium and high frequency magnetic loss and low price have attracted people's attention again and become the main material for preparing integrated molded inductors. On this basis, carbonyl iron powder, iron silicon chromium powder, iron silicon powder, iron-based amorphous, iron-based nanocrystals, etc. are used as powder materials.

[0005] Since the one-piece molded inductor product includes a seat body and a winding body, the seat body is pressed from metal magnetic powder, the winding body is located inside the seat body, and the winding body has lead pins, which are formed on the surface of the seat body. After the pressing is completed, the product is cured at a temperature above 100°C to form strength and meet reliability requirements. Therefore, thermosetting resins such as epoxy resin and phenolic resin are generally used to coat the powder for product production. During the one-piece molding process, since the product contains two different substances, the winding and the magnetic powder, these two different substances may often crack during the thermal curing process due to different expansion coefficients.

[0006] The temperature resistance level of ordinary one-piece molded inductors is generally 85℃, and the highest is 125℃. With the increase in automotive electronic control systems, the temperature of the corresponding working environment has increased. Compared with the higher reliability requirements of automotive electronics, it is necessary to meet the 155℃ / 165℃ / 180℃ temperature resistance level of AEC-Q200. Including 1000 hours of high temperature storage, high temperature and high humidity, cold and hot shock, etc., among which the high temperature load test is the most stringent, and it is necessary to perform high temperature storage tests under power-on and load. Therefore, in order to adapt to higher temperature working environments, it is necessary to give one-piece molded inductors better high temperature resistance.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The object of the present invention is to provide an integrally formed inductor and a method for manufacturing the same, in order to improve at least one of the problems mentioned in the background art.

[0009] The present invention is achieved in that:

[0010] In a first aspect, the present invention provides a method for preparing an integrally formed inductor, comprising:

[0011] Place the winding coil in the mold;

[0012] Filling a mixed powder into a mold, wherein the mixed powder includes composite magnetic powder;

[0013] Die-cast, then heat-cured;

[0014] The components of the composite magnetic powder include: an insulating agent, a first adhesive, a second adhesive, a third adhesive, a low-temperature curing agent, a curing catalyst and passivated magnetic powder;

[0015] The first adhesive is selected from at least one of epoxy resin, phenolic resin and polyurethane, the mass ratio of the first adhesive to the passivated magnetic powder is 1 to 3: 100;

[0016] The second adhesive is a cyanate resin, and the mass ratio of the second adhesive to the first adhesive is 10-50:100;

[0017] The third adhesive is selected from at least one of liquid polysulfide rubber and polycarbonate, and the mass ratio of the third adhesive to the second adhesive is 10-30:100;

[0018] The low temperature curing agent is selected from at least one of m-phenylenediamine, diaminodiphenylmethane and dimethylimidazole, and the mass ratio of the low temperature curing agent to the first adhesive is 1-5:100;

[0019] The curing catalyst is selected from at least one of cobalt isooctanoate and tin isooctanoate, and the mass ratio of the curing catalyst to the second adhesive is 0.5 to 2:100;

[0020] The mass ratio of the insulating agent to the passivated magnetic powder is 0.5~5:100.

[0021] In an optional embodiment, the mixed powder further includes a lubricant, and the mass ratio of the lubricant to the composite magnetic powder is 0.1-0.5:100.

[0022] In an optional embodiment, the lubricant is selected from at least one of zinc stearate, magnesium stearate and magnesium stearate.

[0023] In an optional embodiment, the lubricant is selected from at least one of zinc stearate, magnesium stearate and magnesium stearate.

[0024] In an optional embodiment, before the mixed powder is filled into the mold, the step further includes obtaining composite magnetic powder, and the preparation method of the composite magnetic powder includes:

[0025] The insulating agent, the first adhesive, the second adhesive, the third adhesive, the low-temperature curing agent, the curing catalyst, the passivated magnetic powder and the mixed solvent are uniformly mixed to obtain a first mixture;

[0026] removing the mixed solvent in the first mixed material to obtain a second mixed material;

[0027] The second mixed material is granulated and then baked at a temperature of 40-80° C. for 30-120 min to obtain composite magnetic powder.

[0028] In an optional embodiment, the mixed solvent is selected from at least one of ethanol, acetone, ethyl acetate and methylal;

[0029] The mass ratio of the mixed solvent to the passivated magnetic powder is 5~15:100.

[0030] In an optional embodiment, before obtaining the composite magnetic powder, the process further includes preparing passivated magnetic powder, and the preparation method of the passivated magnetic powder includes:

[0031] The raw powder, the passivation liquid and the passivation solvent are mixed evenly to obtain an intermediate material;

[0032] The passivation solvent in the intermediate material is removed, and then the passivated magnetic powder is obtained by baking at a temperature of 40-80°C for 30-120 minutes;

[0033] The raw powder is selected from at least one of reduced iron powder, carbonyl iron powder, iron silicon chromium powder, iron silicon powder, iron silicon aluminum powder, iron nickel powder, iron-based amorphous powder and iron-based nanocrystalline powder;

[0034] The passivation solution is a solution of at least one of phosphoric acid and phosphate.

[0035] In an optional embodiment, the method further includes at least one of the following features (1) to (6):

[0036] (1) The mass concentration of the passivation solution is 50~85%;

[0037] (2) The phosphate is at least one of monohydrogen phosphate or dihydrogen phosphate of the iron, zinc, magnesium and aluminum series;

[0038] (3) The mass ratio of passivation solution to original powder is 0.1~1:100;

[0039] (4) the passivation solvent is selected from at least one of ethanol, acetone, ethyl acetate and methylal;

[0040] (5) The mass ratio of the passivation solvent to the original powder is 5~15:100;

[0041] (6) The D50 of the original powder is 5~30μm.

[0042] In an optional embodiment, the method further includes at least one of the following features (1) to (3):

[0043] (1) Thermal curing temperature is 160~200℃;

[0044] (2) Die casting pressure is 500~700MPa;

[0045] (3) The insulating agent is selected from at least one of kaolin, mica powder, silicon oxide and aluminum oxide.

[0046] In an optional embodiment, after thermal curing, the step of electrically connecting the lead pins of the winding coil to form solder pads is also included.

[0047] In a second aspect, the present invention provides an integrally formed inductor, which is manufactured using the manufacturing method of any one of the aforementioned embodiments.

[0048] The present invention has the following beneficial effects:

[0049] The preparation method provided by the present invention adopts composite magnetic powder to fill in a mold, and obtains an integrally formed inductor through pressing and heat curing. The composite magnetic powder used in the present invention has a specially designed composition, and a suitable amount of cyanate resin capable of copolymerizing with a first adhesive is added to give the inductor heat resistance. However, since the cyanate resin has a high curing temperature and a long curing time, the addition of the cyanate resin will cause the preparation process to be time-consuming and energy-intensive. Therefore, a curing catalyst is also added to the component, which can greatly reduce the curing time and curing temperature, reduce the curing time to about 1 hour, and reduce the curing temperature to below 180°C, which matches the production process of the integrally formed inductor. Since cyanate resin has a rigid structure and poor toughness, direct addition will cause cracking after thermal curing. Also, since cyanate resin has poor spreading properties, it cannot be well coated on the surface of metal powder and is prone to debonding, which is also a factor that causes thermal curing cracking. Therefore, a suitable amount of liquid polysulfide rubber or polycarbonate is added. The addition of liquid polysulfide rubber or polycarbonate not only increases the viscosity of the adhesive system, so that the cyanate resin can be evenly coated on the surface of the powder, but also increases the toughness of the system, so that the product does not crack. Therefore, the preparation method provided by the present invention can achieve that the material will not crack during the thermal curing process because its adhesive is specially designed. The prepared inductor has high temperature resistance and can be used in high temperature environments. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0051] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0052] In view of the problems existing in the background technology, the following considerations were made:

[0053] The resin used in the preparation process of one-piece molded inductors, taking epoxy resin as an example, the performance of epoxy resin (EP) after curing drops significantly at 70~80℃, and the use temperature of high temperature resistant type does not exceed 130℃, and the performance drops more significantly after moisture absorption. Therefore, improving moisture resistance and temperature resistance are the goals of EP modification. Cyanate ester (CE) is a type of thermosetting resin with low toxicity, high temperature resistance, low moisture absorption and excellent dielectric properties. Its glass transition temperature Tg is 240~280℃, and it can copolymerize with epoxy, making it an ideal high heat-resistant epoxy modifier. However, CE has poor toughness when used alone, and it is easy to crack for one-piece molded inductor products. In addition, the characteristics of CE curing reaction are high curing temperature and long curing time. Studies have shown that cyanate resin without catalyst is cured and heated at 150℃ for 48h, and the monomer conversion rate is only 48%; when cured at 200℃, it takes 7h when the conversion rate reaches 90%, and a higher temperature and longer time are required to achieve complete curing, which makes the CE processing time-consuming and energy-consuming.

[0054] An embodiment of the present invention provides a method for preparing an integrally formed inductor, comprising:

[0055] Place the winding coil in the mold;

[0056] Filling a mixed powder into a mold, wherein the mixed powder includes composite magnetic powder;

[0057] Die-cast, then heat-cured;

[0058] The components of the composite magnetic powder include: an insulating agent, a first adhesive, a second adhesive, a third adhesive, a low-temperature curing agent, a curing catalyst and passivated magnetic powder;

[0059] The first adhesive is selected from at least one of epoxy resin, phenolic resin and polyurethane, the mass ratio of the first adhesive to the passivated magnetic powder is 1 to 3: 100;

[0060] The second adhesive is a cyanate resin, and the mass ratio of the second adhesive to the first adhesive is 10-50:100;

[0061] The third adhesive is selected from at least one of liquid polysulfide rubber and polycarbonate, and the mass ratio of the third adhesive to the second adhesive is 10-30:100;

[0062] The low temperature curing agent is selected from at least one of m-phenylenediamine, diaminodiphenylmethane and dimethylimidazole, and the mass ratio of the low temperature curing agent to the first adhesive is 1-5:100;

[0063] The curing catalyst is selected from at least one of cobalt isooctanoate and tin isooctanoate, and the mass ratio of the curing catalyst to the second adhesive is 0.5 to 2:100;

[0064] The mass ratio of the insulating agent to the passivated magnetic powder is 0.5~5:100.

[0065] The preparation method provided by the present invention adopts composite magnetic powder to fill in a mold, and obtains an integrally formed inductor through pressing and heat curing. The composite magnetic powder used in the present invention has a specially designed composition, and a suitable amount of cyanate resin capable of copolymerizing with a first adhesive is added to give the inductor heat resistance. However, since the cyanate resin has a high curing temperature and a long curing time, the addition of the cyanate resin will cause the preparation process to be time-consuming and energy-intensive. Therefore, a curing catalyst is also added to the component, which can greatly reduce the curing time and curing temperature, reduce the curing time to about 1 hour, and reduce the curing temperature to below 180°C, which matches the production process of the integrally formed inductor. Since cyanate resin has a rigid structure and poor toughness, direct addition will cause cracking after thermal curing. Also, since cyanate resin has poor spreading properties, it cannot be well coated on the surface of metal powder and is prone to debonding, which is also a factor that causes thermal curing cracking. Therefore, a suitable amount of liquid polysulfide rubber or polycarbonate is added. The addition of liquid polysulfide rubber or polycarbonate not only increases the viscosity of the adhesive system, so that the cyanate resin can be evenly coated on the surface of the powder, but also increases the toughness of the system, so that the product does not crack. Therefore, the preparation method provided by the present invention can achieve that the material will not crack during the thermal curing process because its adhesive is specially designed. The prepared inductor has high temperature resistance and can be used in high temperature environments.

[0066] Specifically, the preparation method is:

[0067] (1) First add the raw powder into the mixing equipment.

[0068] Optionally, the raw powder is selected from at least one of reduced iron powder, carbonyl iron powder, iron silicon chromium powder, iron silicon powder, iron silicon aluminum powder, iron nickel powder, iron-based amorphous powder and iron-based nanocrystalline powder.

[0069] Optionally, the D50 of the raw powder is between 5 and 30 μm.

[0070] (2) Add the passivation solution into the mixing equipment.

[0071] Optionally, the passivation solution includes, but is not limited to, a solution of at least one of phosphoric acid and phosphate;

[0072] Furthermore, if the passivation solution is a phosphate solution, the phosphate may be at least one of monohydrogen phosphate or dihydrogen phosphate of iron, zinc, magnesium and aluminum series;

[0073] Furthermore, in order to achieve a good passivation effect, the mass concentration of the passivation solution is 50~85%;

[0074] Furthermore, to ensure that the raw powder is fully passivated, the mass ratio of the passivation solution to the raw powder is 0.1~1:100.

[0075] (3) Add the passivating solvent into the mixing equipment.

[0076] The purpose of adding the passivation solvent is mainly to assist the passivation solution and the original powder to be fully mixed evenly.

[0077] Optionally, the passivation solvent is selected from at least one of ethanol, acetone, ethyl acetate and methylal;

[0078] Optionally, the mass ratio of the added amount of the passivation solvent to the original powder is 5~15:100.

[0079] (4) Stir at a speed of 60-80 rpm for 30-90 min to fully mix the original powder, passivation solution and passivation solvent, then blow dry the passivation solvent and take out the mixture.

[0080] (5) The mixture obtained after drying the passivation solvent is placed in an exhaust oven for low-temperature baking at a drying temperature of 40 to 80° C. and baked for 30 to 120 minutes to obtain the passivated magnetic powder.

[0081] (6) After the passivated magnetic powder is cooled, it is added to the mixing equipment, and the insulating agent, the first adhesive, the second adhesive, the third adhesive, the low-temperature curing agent, the curing catalyst and the mixed solvent are added. The mixture is stirred at a speed of 60-80 rpm for 30-90 minutes to mix the components in the mixing equipment evenly. After that, the mixed solvent is blown dry and the mixture is taken out.

[0082] The addition of mixed solvent can promote the thorough mixing of each component.

[0083] The first adhesive is selected from at least one of epoxy resin, phenolic resin and polyurethane, and the mass ratio of the first adhesive to the passivated magnetic powder is 1-3:100;

[0084] Optionally, the molecular weight of the epoxy resin, phenolic resin or polyurethane is 2000-4000.

[0085] Preferably, the first adhesive is epoxy resin. Epoxy resin and cyanate resin copolymerization can generate high temperature resistant oxazolidinone and isocyanurate, which can significantly improve the high temperature resistance of the inductor. However, the two substances generated will cause the toughness of the inductor to deteriorate. By adding a third adhesive with better toughness, the problem of poor toughness caused by the production of oxazolidinone and isocyanurate can be solved, so that the prepared inductor has better high temperature resistance while ensuring that it does not crack.

[0086] The second adhesive is a cyanate resin, and the mass ratio of the second adhesive to the first adhesive is 10-50:100;

[0087] Optionally, the molecular weight of the cyanate resin is 4000-6000;

[0088] The third adhesive is selected from at least one of liquid polysulfide rubber and polycarbonate, and the mass ratio of the third adhesive to the second adhesive is 10-30:100;

[0089] Optionally, the molecular weight of the liquid polysulfide rubber is 1000-5000, and the molecular weight of the polycarbonate is 7000-12000;

[0090] The low temperature curing agent is selected from at least one of m-phenylenediamine, diaminodiphenylmethane and dimethylimidazole, and the mass ratio of the low temperature curing agent to the first adhesive is 1-5:100;

[0091] The curing catalyst is selected from at least one of cobalt isooctanoate and tin isooctanoate, and the mass ratio of the curing catalyst to the second adhesive is 0.005-0.02:100;

[0092] The mass ratio of insulating agent to passivated magnetic powder is 0.5~5:100;

[0093] Optionally, the insulating agent is selected from at least one of kaolin, mica powder, silicon oxide and aluminum oxide;

[0094] Optionally, the mixed solvent is selected from at least one of ethanol, acetone, ethyl acetate and methylal;

[0095] Optionally, the mass ratio of the added amount of the mixed solvent to the passivated magnetic powder is 5 to 15:100.

[0096] (7) The mixture obtained after drying the mixed solvent is placed in an exhaust oven for low-temperature baking at a drying temperature of 40 to 80° C. and baked for 30 to 120 min to obtain composite magnetic powder.

[0097] (8) After the composite magnetic powder is cooled, a lubricant is added thereto and mixed evenly to obtain a mixed powder.

[0098] Optionally, the lubricant is selected from at least one of zinc stearate, magnesium stearate and magnesium stearate.

[0099] The addition of lubricant can make the inductor easier to press into shape.

[0100] The mass ratio of lubricant to composite magnetic powder is 0.1~0.5:100.

[0101] (9) Place the winding coil in a mold, fill the mold with mixed powder, die-cast, and then thermally cure to obtain a preliminary inductor product;

[0102] Optionally, the pressure during die casting is 500~700MPa;

[0103] Optionally, the thermal curing temperature is 160-200° C. At this temperature, the composite powder can be cured, and the prepared inductor can be better guaranteed to be free of cracks and more resistant to high temperatures.

[0104] (10) The lead pins of the winding coil of the initial inductor are electrically connected to form welding pads to obtain an integrally formed inductor product.

[0105] The one-piece molded inductor provided in the embodiment of the present invention is manufactured by using the manufacturing method provided in the embodiment of the present invention.

[0106] Example 1

[0107] The FeSi chromium powder (FeSi 3.5 Cr 4.5 ) 10000g was added into the mixing equipment, and then 50g of phosphoric acid solution with a mass concentration of 85% and 1000g of ethanol were added into the mixing equipment, and mixed at a speed of 60rpm for 60min to obtain a mixture, and then the ethanol therein was dried, and the mixture was placed in a ventilation oven and baked at 60℃ for 60min to obtain the passivated magnetic powder.

[0108] Add 10000g of cooled passivated magnetic powder, 200g of kaolin, 300g of epoxy resin (brand E51, molecular weight of about 3000), 100g of cyanate resin (bisphenol A type, molecular weight of about 5000), 20g of liquid polysulfide rubber (brand JLY-155, molecular weight of about 4000), 10g of dimethylimidazole, 2g of tin isooctanoate and 1000g of ethanol into a mixing device, stir at a speed of 70rpm for 60min to mix the components in the mixing device evenly, then blow dry the ethanol, place in a ventilation oven and bake at 60℃ for 60min to obtain composite magnetic powder.

[0109] The composite magnetic powder and 20 g of magnesium stearate were uniformly mixed to obtain a mixed powder.

[0110] The winding coil is placed in a mold, filled with mixed powder, die-casted at a pressure of 700 MPa, and then cured at a temperature of 180°C to obtain a preliminary inductor product.

[0111] The lead pins of the winding coil of the initial inductor are electrically connected to form welding pads to obtain an integrally formed inductor finished product.

[0112] Example 2

[0113] This embodiment is basically the same as Embodiment 1, except that:

[0114] Add 10000g of cooled passivated magnetic powder, 50g of kaolin, 100g of epoxy resin (brand E51, molecular weight of about 3000), 50g of cyanate resin (bisphenol A type, molecular weight of about 5000), 5g of liquid polysulfide rubber (brand JLY-155, molecular weight of about 4000), 0.1g of dimethylimidazole, 0.25g of tin isooctanoate and 500g of ethanol into a mixing device, stir at a speed of 60rpm for 60min to mix the components in the mixing device evenly, then blow dry the ethanol, place in a ventilation oven and bake at 40°C for 120min to obtain composite magnetic powder.

[0115] 1000 g of the composite magnetic powder and 1 g of magnesium stearate were mixed evenly to obtain a mixed powder.

[0116] The winding coil is placed in a mold, filled with mixed powder, die-casted at a pressure of 500 MPa, and then cured at a temperature of 160° C. to obtain a preliminary inductor product.

[0117] Example 3

[0118] This embodiment is basically the same as Embodiment 1, except that:

[0119] Add 10000g of cooled passivated magnetic powder, 500g of kaolin, 300g of epoxy resin (brand E51, molecular weight of about 3000), 30g of cyanate resin (bisphenol A type, molecular weight of about 5000), 9g of liquid polysulfide rubber (brand JLY-155, molecular weight of about 4000), 15g of dimethylimidazole, 0.6g of tin isooctanoate and 1500g of ethanol into a mixing device, stir at a speed of 80rpm for 60min to mix the components in the mixing device evenly, then blow dry the ethanol, place in a ventilation oven and bake at 80℃ for 30min to obtain composite magnetic powder.

[0120] 1000 g of the composite magnetic powder was mixed with 5 g of magnesium stearate to obtain a mixed powder.

[0121] The winding coil is placed in a mold, filled with mixed powder, die-casted at a pressure of 700 MPa, and then cured at a temperature of 200°C to obtain a preliminary inductor product.

[0122] Example 4

[0123] This embodiment is substantially the same as embodiment 1, and the differences are shown in Table 1.

[0124] Comparative Example

[0125] Comparative Examples 1 to 13 are provided, which are substantially the same as Example 1, except for the differences shown in Table 1.

[0126] Table 1 Parameter comparison between comparative examples and embodiment 1

[0127]

[0128] Experimental example

[0129] (1) Observe whether the inductor has cracks on its appearance;

[0130] (2) Change rate of induction value after 1000h, 155℃ high temperature load;

[0131] (3) Test the initial inductance value of the inductor with no cracks or small cracks.

[0132] Record the test results in Table 2.

[0133] Table 2 Test results of various embodiments and comparative examples

[0134]

[0135] In Table 1, "large crack" means that the crack length accounts for more than 50% of the single-direction size of the entire device, "small crack" means that the crack length accounts for less than 50% of the single-direction size of the entire device, and "no crack" means that there are no cracks visible to the naked eye.

[0136] It can be seen from Table 1 that the inductors prepared in various embodiments provided by the present invention are not cracked and the change rate of the inductance value after high temperature load is less than 10%.

[0137] Comparative Examples 1 and 8 are traditional processes, and the rate of change of the induction value after high temperature load far exceeds the required 10%.

[0138] Comparative Example 2, pure cyanate ester resin, was not completely cured and the product cracked severely, but its heat resistance was much better than that of Comparative Examples 1 and 8.

[0139] After adding the accelerator to the cyanate resin in Comparative Examples 3 and 9, the products still cracked. However, due to the complete curing, the heat resistance was improved compared with Comparative Example 2.

[0140] Comparative Examples 4 and 10: Copolymerization of epoxy resin and cyanate resin can generate oxazolidinone and isocyanate urea with better high temperature resistance, and the heat resistance is improved compared with Comparative Examples 1 and 8, but the product cracks.

[0141] In Comparative Examples 5 and 11, after adding low-temperature epoxy curing agent to epoxy resin and cyanate resin, cracking is reduced and heat resistance is lower than that of Comparative Examples 4 and 10.

[0142] In Comparative Examples 6 and 12, cyanate resin accelerator was added to epoxy resin and cyanate resin, and the product cracked, and the heat resistance was improved compared with Comparative Examples 4 and 10.

[0143] In comparative examples 7 and 13, all reagents were added, and small cracks still occurred in the product molding, but the heat resistance met the requirements.

[0144] In particular, when Example 4 is compared with Comparative Examples 1 and 7 to 13, while its high temperature resistance is improved, its initial sensitivity is not worse than that of each comparative example.

[0145] Summary: In epoxy resin and cyanate resin systems, adding low-temperature epoxy curing agent can improve molding, and adding accelerator can improve the degree of curing reaction and improve heat resistance. If the second adhesive, third adhesive, low-temperature curing agent or curing catalyst is missing, it is impossible to obtain a crack-free and high-temperature resistant inductor.

[0146] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an integrally formed inductor, characterized in that: include: Place the winding coil in the mold; Filling a mixed powder into a mold, wherein the mixed powder includes composite magnetic powder; Die-cast, then heat-cured; The components of the composite magnetic powder include: an insulating agent, a first adhesive, a second adhesive, a third adhesive, a low-temperature curing agent, a curing catalyst and passivated magnetic powder; The first adhesive is selected from at least one of epoxy resin, phenolic resin and polyurethane, and the mass ratio of the first adhesive to the passivated magnetic powder is 1 to 3: 100; The second adhesive is a cyanate resin, and the mass ratio of the second adhesive to the first adhesive is 10-50:100; The third adhesive is selected from at least one of liquid polysulfide rubber and polycarbonate, and the mass ratio of the third adhesive to the second adhesive is 10-30:100; The low-temperature curing agent is selected from at least one of m-phenylenediamine, diaminodiphenylmethane and dimethylimidazole, and the mass ratio of the low-temperature curing agent to the first adhesive is 1-5:100; The curing catalyst is selected from at least one of cobalt isooctanoate and tin isooctanoate, and the mass ratio of the curing catalyst to the second adhesive is 0.5 to 2:100; The mass ratio of the insulating agent to the passivated magnetic powder is 0.5-5:

100.

2. The method for preparing an integrally formed inductor according to claim 1, characterized in that: The mixed powder also includes a lubricant, and the mass ratio of the lubricant to the composite magnetic powder is 0.1-0.5:

100.

3. The method for preparing an integrally formed inductor according to claim 2, characterized in that: The lubricant is selected from at least one of zinc stearate, magnesium stearate and magnesium stearate.

4. The method for preparing an integrally formed inductor according to claim 1, characterized in that: Before filling the mixed powder into the mold, the method further includes obtaining the composite magnetic powder. The preparation method of the composite magnetic powder includes: The insulating agent, the first adhesive, the second adhesive, the third adhesive, the low-temperature curing agent, the curing catalyst, the passivated magnetic powder and the mixed solvent are uniformly mixed to obtain a first mixed material; removing the mixed solvent in the first mixed material to obtain a second mixed material; The second mixed material is granulated, and then baked at a temperature of 40-80° C. for 30-120 min to obtain the composite magnetic powder.

5. The method for preparing an integrally formed inductor according to claim 4, characterized in that: The mixed solvent is selected from at least one of ethanol, acetone, ethyl acetate and methylal; The mass ratio of the mixed solvent to the passivated magnetic powder is 5-15:

100.

6. The method for preparing an integrally formed inductor according to claim 1, characterized in that: Before obtaining the composite magnetic powder, the method further includes preparing the passivated magnetic powder. The preparation method of the passivated magnetic powder includes: The raw powder, the passivation liquid and the passivation solvent are mixed evenly to obtain an intermediate material; Removing the passivation solvent in the intermediate material, and then baking at a temperature of 40-80° C. for 30-120 min to obtain the passivated magnetic powder; The raw powder is selected from at least one of reduced iron powder, carbonyl iron powder, iron silicon chromium powder, iron silicon powder, iron silicon aluminum powder, iron nickel powder, iron-based amorphous powder and iron-based nanocrystalline powder; The passivation solution is a solution of at least one of phosphoric acid and phosphate.

7. The method for preparing an integrally formed inductor according to claim 6, characterized in that: It also includes at least one of the following features (1) to (6): (1) The mass concentration of the passivation solution is 50-85%; (2) The phosphate is at least one of monohydrogen phosphate or dihydrogen phosphate of iron, zinc, magnesium and aluminum series; (3) The mass ratio of the passivation solution to the original powder is 0.1~1:100; (4) The passivation solvent is selected from at least one of ethanol, acetone, ethyl acetate and methylal; (5) The mass ratio of the passivation solvent to the original powder is 5-15:100; (6) The D50 of the raw powder is 5~30μm.

8. The method for preparing an integrally formed inductor according to claim 1, characterized in that: It also includes at least one of the following features (1) to (3): (1) Thermal curing temperature is 160~200℃; (2) Die casting pressure is 500~700MPa; (3) The insulating agent is selected from at least one of kaolin, mica powder, silicon oxide and aluminum oxide.

9. The method for preparing an integrally formed inductor according to claim 1, characterized in that: After thermal curing, the method further includes electrically connecting the lead pins of the winding coil to form a soldering pad.

10. An integrally formed inductor, characterized in that: The inductor is manufactured by the method for manufacturing an integrally formed inductor as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Iron-based amorphous powder and method for preparing coil-embedded integral-forming inductor

    CN103273068A

  • Preparation method of chip inductor

    CN114758881A